Energy saving opportunities in integrated NGL/LNG schemes exploiting: Thermal-coupling common-utilities and process knowledge - Khan, M.; Chaniago, Y.; Woldetensay, Mesfin; Lee, M. (Elsevier BV, 2014)
Novel integrated and optimization schemes for natural gas (NG) liquid recovery and liquefaction step are presented. The liquefaction of NG was carried out using the newly developed KSMR liquefaction cycle while the separation of NG liquids was performed using energy efficient thermally coupled distillation schemes. The main highlight of integration are, (i) feed splitting to provide reboiler duty in the methane scrubber, (ii) common refrigeration utilities required all over the plant; and (iii) flexibility of integrated plant for easy transition between ethane recovery or ethane rejection. These integration steps minimize the overall plant-specific power requirements and the duplication of processing equipment. After successful integration, the MR cycle was optimized for the compression energy requirement by varying the refrigerant composition and operating pressure levels with the aid of an in-house established knowledge-based optimization (KBO) methodology. The KBO approach is robust in application and gives consistent results. Compared to the base case, 9% improvement in plant compression energy requirement was obtained.